The siliconvalization of work. An argentine experience - Patricia Ventrici; Hernan Palermo (Íconos)
Any discussion about digital or algorithmic technologies leads us immediately into the already protracted debate about which stage of capitalism are we in right now. The current context spawns a “new race” of high-tech based entrepreneurs and firms who lead the fast-growing so-called “unicorn” locally-based multinational businesses. In the present article we use a case study about the “Free Market” in Argentina in order to study the key ideas behind the discourse sponsored by those firms. We have privileged a qualitative methodology supported by an intense previous field work based on in several sources: unstructured interviews, participant observation, secondary documents and photographic materials. The study finds that the new discourses are intertwined with the new technological advances in order to shore up novel capital-labor relationships which support new forms of workplace organization, and, furthermore, a new self- understanding of the worker. These discourses are buttressed by concepts such as “entrepreneurism” and “meritocracy”, which develop into more or less explicit notions centered on terms such as “success”, “future”, “democracy”, “gender” among others. Cognitive capitalism has sanctioned a new brand of firms and entrepreneurs who subscribe to the “Silicon Valley” model. This model has strongly spread in Latin America, and more specifically in Argentina.